Effect of Hydrophilic- Lipophilic Balance (HLB) Value on the Stability of Cosmetic Lotion Based on Walnut Oil (Canarium Indicium L.) Oil-in-Water Emulsion - Putri, Alza Izmuliana Eka; Ariyanto, Hermawan Dwi (Journal of Vocational Studies on Applied Research, 2022)
Walnut oil is high source of fatty acid especially oleic acid compare to coconut oil. It has about 40-70% of oleic acid and suitable as moisturizing agent, anti-inflammatory and which contains antioxidants that are good for skin health as a primary ingredient for lotion. This study aims to determine the effect hydrophilic-lipophilic balance (HLB) on the stability of emulsion as a lotion material. The oil-in-water emulsion was formed by emulsification process using Ultra Turrax homogenizer (8000 and 32000 rpm) with addition of tween 80 and span 80 as emulsifiers. Completed randomized design and analysis of variance were used to determine the significant parameters on the stability of emulsion: homogeneity, creaming index, viscosity, density and morphology. Emulsion with the highest stability is sample 8 which is formed at 14.5 HLB value and 32000 rpm homogenizer speed during 5 min. It has complied with SNI-16-4399-1996.